2015
DOI: 10.12989/sem.2015.54.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modelling and lifecycle performance assessment of bond strength of corroded reinforcement in concrete

Abstract: Life cycle performance of corrosion affected RC structures is an important and challenging issue for effective infrastructure management. The accurate condition assessment of corroded RC structures mainly depends on the effective evaluation of deterioration occurring in the structures. Structural performance deterioration caused by reinforcement corrosion is a complex phenomenon which is generally uncertain and non-decreasing. Therefore, a stochastic modelling such as the gamma process can be an effective tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…As a result, reinforcement corrosion becomes an important factor affecting the safety and durability of reinforced concrete structures. The literature [6] showed that since reinforcement corrosion also significantly reduces the load-carrying capacity of beams and ultimately affects the service performance of RC structures, detecting reinforcement corrosion inside concrete has become an important task. Researchers often use several NDT methods between electrochemical, physical, and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, reinforcement corrosion becomes an important factor affecting the safety and durability of reinforced concrete structures. The literature [6] showed that since reinforcement corrosion also significantly reduces the load-carrying capacity of beams and ultimately affects the service performance of RC structures, detecting reinforcement corrosion inside concrete has become an important task. Researchers often use several NDT methods between electrochemical, physical, and analytical methods.…”
Section: Introductionmentioning
confidence: 99%